The Story of Resistance: How Do Social Movements Tell Their Stories - Turgut, H. (IGI Global, 2022)
In today’s world, it’s impossible to think about social movements apart from the media, and it has become an obligation out of necessity to set alternative media channels in terms of social movements. The new media and social media networks have been used actively in the process of setting aforementioned alternative media channels. The use of alternative media as a means of criticism and resistance becomes possible with these media networks when they are used with effective communication strategies and techniques. Transmedia storytelling is the leading one among these effective communication strategies. Based on this assertion, in this study, how transmedia storytelling was used as a political advertising activity by the social movements will be analyzed through the example of Gezi Park protests that took place in Turkey in 2013. © 2023 by IGI Global. All rights reserved.